(untitled) (Discourse of Law and Administration, 2021)
The article was devoted to the analysis of the so-called administrative detention, referred to in Article 40 paragraph 1 of the Act on Upbringing in Sobriety and Counteracting Alcoholism. The author searches for answers to questions about the limits of legitimacy of police actions when administratively detaining a citizen. She also analyses whether a person under the influence of alcohol can be arrested and taken to a so be ring station in every case, and discusses the consequences of an illegal arrest both from the point of view of the arrested person and the responsibility of the arresting officer.